2014
DOI: 10.1371/journal.pone.0108679
|View full text |Cite
|
Sign up to set email alerts
|

Validating and Extending the Three Process Model of Alertness in Airline Operations

Abstract: Sleepiness and fatigue are important risk factors in the transport sector and bio-mathematical sleepiness, sleep and fatigue modeling is increasingly becoming a valuable tool for assessing safety of work schedules and rosters in Fatigue Risk Management Systems (FRMS). The present study sought to validate the inner workings of one such model, Three Process Model (TPM), on aircrews and extend the model with functions to model jetlag and to directly assess the risk of any sleepiness level in any shift schedule or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Additional background information was collected using a form with questions on age, sex, marital status, education level, and current occupation and questions on psychiatric diagnoses and problems, medication use, and morning-eveningness. More specifically, for type of ADHD, patients were asked to choose which described their type best: Predominantly inattentive, Predominantly hyperactive/impulsive, Combined subtype, or NOS; for psychiatric diagnoses an open-ended question was used; for psychiatric problems during the last year, patients were given a list and asked to mark which applied to them; medication use was gauged with an open ended questions with examples, and medications were classified according to stated use and/or substance; circadian type was measured with the question on morning-eveningness from the Karolinska Sleep Questionnaire, on a five point scale (Extreme morning type, morning type, intermediate type, evening type, extreme evening type) [33].…”
Section: Methodsmentioning
confidence: 99%
“…Additional background information was collected using a form with questions on age, sex, marital status, education level, and current occupation and questions on psychiatric diagnoses and problems, medication use, and morning-eveningness. More specifically, for type of ADHD, patients were asked to choose which described their type best: Predominantly inattentive, Predominantly hyperactive/impulsive, Combined subtype, or NOS; for psychiatric diagnoses an open-ended question was used; for psychiatric problems during the last year, patients were given a list and asked to mark which applied to them; medication use was gauged with an open ended questions with examples, and medications were classified according to stated use and/or substance; circadian type was measured with the question on morning-eveningness from the Karolinska Sleep Questionnaire, on a five point scale (Extreme morning type, morning type, intermediate type, evening type, extreme evening type) [33].…”
Section: Methodsmentioning
confidence: 99%
“…of the person [ 12 15 ]. Therefore, along with the knowledge of basic features of the brain activity in solving particular tasks, it is of great practical importance to study the influence of the human factors, such as responsibility, motivation, attention, and stress [ 16 , 17 ]. In this context, the neurophysiological research of visual perception focused on the detection of brain activity and interactions between different brain regions [ 18 22 ] demonstrated an increased activity in various brain areas, especially in the occipital cortex [ 18 , 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our finding is relevant, as unintentional sleep at work may compromise the safety of flights and it is a reflection of the conditions and organization of work of Brazilian airline pilots 12 . According to Cabon et al 3 , pilots who fly long distances are particularly susceptible to lapses during vigil, as well as during periods of low workload.…”
Section: Discussionmentioning
confidence: 65%
“…Ingre et al 12 have observed that unintentional sleep at work is a reflection of the work conditions and organization of pilots. The authors 12 have also shown that unintentional sleep at work may compromise the safety of flights.…”
Section: Introductionmentioning
confidence: 99%